Gynaecological Endoscopy. Complications and risks of laparoscopy. - Díaz Huamán, Víctor (2015)
The pelviscopy or gynecological endoscopy showed a renewed interest from the 1950s, allowing the gynecologist count with a diagnostic and surgical techniques in matched in this, bringing it to a total boom, spreading in our country as it did in the world opportunity. It was expected, like any other instrumented technique, with the increasing use of this resource, describing complications, even in experienced hands. Most of them occur when used as surgical sterilization resource and biopsies of organs.